Prevalence of Human Brucellosis in the Southern Zone of Sidi-Bel-Abbes, Algeria - Abdelkader, Ammam; Reda, Belmamoun Ahmed; Karima, Grele (Archives of Clinical and Medical Case Reports, 2018)
Brucellosis is an anthropozoonosis caused by a bacterium of the genus brucella. The aim of this study was to study the seroprevalence of brucellosis in high risk individuals. The Wright technique was used (Reagent: Brucella abortus, Antigen: Somatic, Reference: 1205091). Our study focused on the population of the southern region of Sidi-Bel-Abbès and showing clinical signs of brucellosis between February 2010 and June 2012 and whose "Wright" test was positive. 111 cases of human brucellosis have been identified; 59.45% male against 40.54% female. 50.45% reported no contact with animals, however contact with goats, cattle and sheep was 13.51%, 6.30% and 0.90%, respectively. Regarding the consumption of raw milk it was of the order of 53.15% against 17.11% for curd and 0.90% for under cooked meat. The 30-40 age group was the most common. The results on the follow-up of a previous treatment indicate that 2.70% followed a previous treatment against 97.29% that they had no treatment to follow. Brucellosis is an infection that is evolving in our region (Sidi-Bel-Abbès) it requires more monitoring.